Morphology controllable urchin-shaped bimetallic nickel-cobalt oxide/carbon composites with enhanced electromagnetic wave absorption performance. (10th June 2023) - Li, Fushan; Li, Qiuyu; Kimura, Hideo; Xie, Xiubo; Zhang, Xiaoyu; Wu, Nannan; Sun, Xueqin; Xu, Ben Bin; Algadi, Hassan; Pashameah, Rami Adel; Alanazi, Abdullah K.; Alzahrani, Eman; et al.
Highlights: Urchin-like NiCo2 O4 /C composites were synthesized. Oxygen vacancies were introduced into the prepared composites;. Bandwidth of 8.96 GHz at 2 mm was achieved for electromagnetic wave absorber. Analysis of the absorption mechanism of NiCo2 O4 /C absorbers was investigated. Abstract: The microscopic morphology of electromagnetic wave absorbers influences the multiple reflections of electromagnetic waves and impedance matching, determining the absorption properties. Herein, the urchin-shaped bimetallic nickel-cobalt oxide/carbon (NiCo2 O4 /C) composites are prepared via a hydrothermal route, whose absorption properties are investigated by different morphologies regulated by changing calcination temperature. A minimum reflection loss (RLmin ) of -75.26 dB is achieved at a matching thickness of 1.5 mm, and the effective absorption bandwidth (EAB) of 8.96 GHz is achieved at 2 mm. Multi-advantages of the synthesized NiCo2 O4 /C composites contribute to satisfactory absorption properties. First, the interweaving of the needle-like structures increases the opportunities for scattering and multiple reflections of incident electromagnetic waves, and builds up a conductive network to facilitate the enhancement of conductive losses. Second, the carbon component in the NiCo2 O4 /C composites enhances the interfacial polarization and reduces the density of the absorber. Besides, generous oxygen vacancy defects are introduced into the NiCo2 O4 /C composites, which induces defect polarization and dipole polarization. In summary, the ternary coordination of components, defects and morphology led to outstanding electromagnetic wave absorption, which lightened the path for improving the electromagnetic wave absorption property and enriching the family of NiCo2 O4 absorbers with excellent performance.